2021
DOI: 10.1002/acr.24473
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Distribution of Sacroiliac Joint Lesions on Magnetic Resonance Imaging in Patients With Axial Spondyloarthritis and Control Subjects: A Prospective Cross‐Sectional Study, Including Postpartum Women, Patients With Disc Herniation, Cleaning Staff, Runners, and Healthy Individuals

Abstract: Objective To investigate the anatomic location and distribution of lesions on magnetic resonance imaging (MRI) in the sacroiliac (SI) joints in patients with axial spondyloarthritis (SpA), women with and without postpartum pain (childbirth within 4–16 months), patients with disc herniation, cleaning staff, runners, and healthy persons. Methods In a prospective cross‐sectional study of 204 participants, MRI of the entire cartilaginous compartment of the SI joint was scored blindly by 2 independent, experienced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 26 publications
(81 reference statements)
3
17
0
Order By: Relevance
“…Topographic distribution of SIJ BME has been poorly studied in patients with ax-SpA and no preferential localization has been identified. Recently, two studies have provided new information: BME was found throughout the joint, without predominance for the iliac or sacral bone, the upper or lower part and the anterior or posterior part [9,33]. BME associated with ax-SpA is usually bilateral unlike BME unrelated to ax-SpA which is almost exclusively unilateral [33,34].…”
Section: -Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Topographic distribution of SIJ BME has been poorly studied in patients with ax-SpA and no preferential localization has been identified. Recently, two studies have provided new information: BME was found throughout the joint, without predominance for the iliac or sacral bone, the upper or lower part and the anterior or posterior part [9,33]. BME associated with ax-SpA is usually bilateral unlike BME unrelated to ax-SpA which is almost exclusively unilateral [33,34].…”
Section: -Discussionmentioning
confidence: 99%
“…Recently, two studies have provided new information: BME was found throughout the joint, without predominance for the iliac or sacral bone, the upper or lower part and the anterior or posterior part [9,33]. BME associated with ax-SpA is usually bilateral unlike BME unrelated to ax-SpA which is almost exclusively unilateral [33,34]. BME at the lower and posterior part of SIJ is often considered specific to inflammatory diseases and particularly ax-SpA whereas BME can also be observed at these locations in non-inflammatory conditions [16].…”
Section: -Discussionmentioning
confidence: 99%
“…A common example would be a marathon runner with enthesitis of the Achilles tendon who also happens to have some stress-related bone marrow edema at the SIJ in MRI [33,34]. This patient would fulfil the ASAS classification criteria, whereas the probability for an axSpA diagnosis might be quite small.…”
Section: Clinical Diagnosis Vs Classificationmentioning
confidence: 99%
“…The anatomic distribution of inflammatory and structural lesions in a large cohort of patients with and without SpA has previously been investigated in a single study. 13 Division of the SI joint to enable easy analysis seems indispensable in current practice, as it has been suggested that some segments are preferentially associated with the inflammatory or mechanical origin of the lesions. 13 In this retrospective study, we aimed to analyse and compare the anatomic distribution of structural and inflammatory lesions present on the MRI of SI joint in patients with and without SpA, including, as in current practice, patients with non-specific low back pain, women with obstetric history, and athletes, with no age restrictions.…”
Section: Introductionmentioning
confidence: 99%